Pre-mortem analysis in executing new ferronickel plant at halmahera timur to ensure a successful project delivery - Pratomo, Adam; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2016)
Abstract - At the end of 2015, PT. ANTAM (Persero) Tbk. have earned the State Capital Investment funds (PMN) as government support to the State Owned Enterprises to carry out the mandate of Act No. 4 year 2009 (which became effective on January 12, 2014). Fund of Rp. 3.5 trillion will be used to build a ferronickel plant in East Halmahera through the project team P3FH (Proyek Pembangunan Pabrik FeNi Haltim). The challenge for ANTAM is optimize PMN fund to build new plant so that no more additional time and money needed to complete the plant. In order to ensure project a successful project delivery, we have to know what risks that will face the project and how to assessment the high priority and mitigate it. Primary data are collected by conducting interview to several employees with different background to enhance the view of projectâ€™s risk. Secondary used in this study are company data, literature and third party data. Pre-mortem analysis used to encompass the idea of sharing expertise or experience and from this analysis we acquired as many as 26 issues/risks (failure mode) and 59 causes risks, all of them are categorized as the five types of groups: completion, financial, operational, environment, and legal / politics issue/risks. Failure Mode Effect Analysis (FMEA) is used to assess the risk priority obtained from pre-mortem analysis to obtain the 16 highest priority cause risks from several failure mode; Deal and delay with IPP, insufficient fund, failure in performance test, contractual risk, changes in management, possibility of inadequate source of fund and decrease in nickel price. Those issues are related to the completion issue and financial issues/risks. Mitigation on high priority causes risks was elaborate in this study and risks that have top priority here should receive more attention by ANTAM management.Â Keywords: pre-mortem, failure mode effect analysis, completion issues, financial issues, operational issues, environment issues, and legal / politics issue